2021
DOI: 10.1017/s1366728920000826
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual acquisition of reference: The role of language experience, executive functions and cross-linguistic effects

Abstract: The present study aims to understand which factors contribute to different patterns of use of referring expressions by bilingual children, by considering the triangulation between language experience and proficiency, executive functions and cross-linguistic effects. We analyze reference use in Greek in the context of a narrative elicitation task as performed by 125 children of different language combinations, including Greek–Albanian, Greek–English and Greek–German. We calculate, for each child, an index of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 74 publications
2
38
0
Order By: Relevance
“… Serratrice and De Cat (2020) reported that working memory positively correlated with 5-7-year-old bilingual children’s ability to use informative REs for anaphoric reference in English in the presence of a discourse competitor. Torregrossa et al (2021) , however, did not observe any correlation between updating skill (which hinges on working memory) and the production of underspecified pronouns (null subjects and clitics) in Greek in an elicited narration task with Greek-Albanian, Greek-English, and Greek-German bilingual children (7-13-year-old).…”
Section: Reference Production: Linguistic Input and Cognitive Factorsmentioning
confidence: 65%
See 1 more Smart Citation
“… Serratrice and De Cat (2020) reported that working memory positively correlated with 5-7-year-old bilingual children’s ability to use informative REs for anaphoric reference in English in the presence of a discourse competitor. Torregrossa et al (2021) , however, did not observe any correlation between updating skill (which hinges on working memory) and the production of underspecified pronouns (null subjects and clitics) in Greek in an elicited narration task with Greek-Albanian, Greek-English, and Greek-German bilingual children (7-13-year-old).…”
Section: Reference Production: Linguistic Input and Cognitive Factorsmentioning
confidence: 65%
“… Nilsen and Graham (2009) and Serratrice and De Cat (2020) studied preschoolers performing referential communication tasks, and measured cognitive skills by memory of objects and/or backward digit span (BDS). Torregrossa (2017) and Torregrossa et al (2021) elicited oral narratives from school-age children, with cognitive skills measured by BDS and a 2-back task, respectively.…”
Section: Reference Production: Linguistic Input and Cognitive Factorsmentioning
confidence: 99%
“…Bilingual children in Andreou et al’s (in press) study exhibited extensive use of null subject pronouns in Italian and this effect was modulated by language dominance, which was measured through current language and literacy activities. Similarly, Torregrossa et al’s (2021) study has examined the use of under-informative and over-informative referring expressions in Greek with bilingual children speaking three different language pairs, namely, Greek–Albanian, Greek–English and Greek–German. Their study revealed that language experience and proficiency in the non-target language (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study investigated bilingual children acquiring Greek as their societal language. It reported over-informativeness and under-informativeness of referential expressions in referential use as related to the child's language experience (Torregrossa, Andreou, Bongartz & Tsimpli, 2021). This finding might question the assumption of language-universality of referential expressions.…”
Section: Bilingualism and Informativenessmentioning
confidence: 94%